1997
DOI: 10.1021/jo9701748
|View full text |Cite
|
Sign up to set email alerts
|

Dimers and Model Monomers of Nickel(II) Octaethylporphyrin Substituted by Conjugated Groups Comprising Combinations of Triple Bonds with Double Bonds and Arenes. 1. Synthesis and Electronic Spectra

Abstract: Porphyrin dimers linked in the meso-positions by bridges containing alkynes conjugated with the porphyrin π-systems display highly perturbed electronic absorption spectra. We have prepared a series of such dimers using meso-ethynyl nickel(II) octaethylporphyrin as the primary building block. The bridging units include diethynylbenzenes, 2,5-diethynylthiophene, hexenediyne, octatetrayne, butenyne, hexenediyne, and octadienediyne. Some meso-to-β dimers were also made. The dimers are complemented by a set of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 37 publications
4
56
0
1
Order By: Relevance
“…This was observed in earlier work done by the Arnold group involving porphyrins with acetylene linkers, [53] and by others working in different fields. [54][55][56][57][58][59] We find it to be a very convenient and highyielding method.…”
Section: Resultssupporting
confidence: 67%
“…This was observed in earlier work done by the Arnold group involving porphyrins with acetylene linkers, [53] and by others working in different fields. [54][55][56][57][58][59] We find it to be a very convenient and highyielding method.…”
Section: Resultssupporting
confidence: 67%
“…1-Oxyl-2,2,5,5-tetramethylpyrrolin-3-acetylene (TPA) 4 [29] and 3-(4 0 -Iodo-biphenyl-4-ylethynyl)-2,2,5,5-tetramethylpyrrolin-1-oxyl 5 [10] were prepared by procedures described earlier. Cu(meso-ethynyl-OEP) 6 and Ni(meso-ethynyl-OEP) 7 were prepared according to references [16,30] and used as obtained, due to the products susceptibility to spontaneous oxidative dimerisation [31].…”
Section: Synthesismentioning
confidence: 99%
“…This method has been widely used to synthesize porphyrins with ethyne-linked functional groups [11][12][13][14][15]. Although porphyrins with 2-pyridine-ethynyl substituents were expected to be the products according to the method, we found that nickel porphyrins with 2-pyridine-acetyl substituents were in fact the major products (Fig.…”
Section: Resultsmentioning
confidence: 96%